Performance Optimization of Cylindrical WGM Microresonator Sensors for Various Delivery Fiber Diameters - Hassan, Esraa A.; Al-mfrji, Alhuda A.; Mahmood , Aseel I. (Al-Nahrain Journal for Engineering Sciences, 2025)
Whispering Gallery Mode Micro-Resonators (WGMRs) have received significant interest due to their great sensitivity to environmental changes, compact size, and ability to operate over a wide spectral range because their low optical losses produce high-quality factors so that they can be used in various sensing applications. This work investigates the design and implementation of cylindrical WGMRs for Refractive Index (RI) sensing for different delivery fiber diameters. Single Mode Fiber with different waist diameters (80,67.1,18) µm were used as delivery fibers. At the same time, the sensor (resonator) fiber is SMF with a diameter (125 µm). Quality factors and Free Spectral Range (FSR) were calculated and analyzed for each diameter. The quality factor for all diameters was in power of 104, which is considered good. The FSR is inversely proportional to fiber diameter. FSR values were (0.678,1.75,2.03) nm for (80,67.1,18) µm delivery fiber diameters respectively. An analyte prepared by NaCl with different refractive indices is used to investigate the RI sensor performance. Higher sensitivity is obtained from the WGMR with a smaller waist diameter, which is (-)74 nm/RIU. While for the delivery fiber diameters (80,67.1) µm were (-0.28, -9.27) nm/RIU respectively. The submitted sensor will have a good contribution in the field of chemical, biological and medical applications.